Predictors of Intention to Quit Smoking among Patients with Noncommunicable Disease in Thammasat University - Yoosookcharoen, Jutarat; Sumpowthong, Kaysorn; Chompook, Pornthip (Journal of Public Health Nursing, 2018)
Different predictors of intention to quit smoking among patients with noncommunicable disease were studied using the theory of planned behavior (TPB). Subjects comprised outpatients at Thammasat University Hospital, Bangkok, Thailand. Data were gathered using questionnaires, and measuring behavioral attitudes, subjective norms, perceived behavioral control and intention to quit smoking. Data were statistically analyzed by frequency, percentage, mean, and standard deviation using a chi-squared test and binary logistic regression. The results indicated that the mean score of sample intention to quit smoking was 4.17 with standard deviation (SD) 0.51. Attitude toward quitting smoking was 82.81 with S.D 22.89. Subjective norm was 65.39 with SD 17.70. Perceived behavioral control was 78.54 with SD 23.20. Significant relationships were found between sample education, attitude toward quitting smoking, subjective norms and perceived behavioral control (p<0.05). Perceived behavioral control could predict subjects’ intention to quit smoking significantly (p<0.05, OR Adj=3.39, 95% CI: 1.26-9.12). The factor was predictive of 20% of results.These findings suggested that effective smoking cessation programs should focus on empowerment, individual counseling, motivation information and family involvement Valued at 82.81